Enterocolitis necrosante y sus factores predisponentes en los neonatos nacidos en el Hospital Isidro Ayora en el periodo 2014 - Maza Quezada, Gerardo Omar (2015)
This study aims to determine the main predisposing factors for necrotizing enterocolitis (ECN), and its incidence also establish the predisposing factors in preterm infants with NEC. This allows us to avoid the progression of the disease, also reduce exposure to these factors because it is one of the leading causes of morbidity and mortality in neonates. It is important to have a clear perspective of this problem so that a qualitative and quantitative, descriptive, correlational and cross-sectional cohort study was conducted; Universe: I include 342 term and preterm infants, hospitalized in the Neonatal Unit service of Isidro Ayora Hospital. Sample: including 51 infants diagnosed with enterocolitis. Data collection instrument used was a form of data collection and neonatal medical records. As a result it was found that the study sample of the 17.52% of patients had necrotizing enterocolitis, predisposing factors include: respiratory distress with 88.23%, with 58.82% Prematurity, low birth weight with 54.9%, 52.9% male gender, enteral feeding formulas 47.05%, which are the most prevalent. Knowing the factors will help us to employ preventative measures and timely treatment and reduce complications. Key words: Necrotizing enterocolitis and predisposing factors.